Amulets in Roman Religion - Qaddouri, Solaf Abdul Muttalib; Sabaa, Zainab Salman; Mohammed Ali, Hajer Basim (Journal of Posthumanism, 2025)
Ancient civilizations such as Mesopotamian civilization, ancient Egyptian civilization, and the Roman civilization recognized the phenomenon of the widespread use of amulets. It received great attention from the population, and due to the expansion of the Roman Empire over vast areas that included large parts of the inhabited world, and in light of the exploration of the phenomenon which is the subject of this research, interest in it increased, and new patterns of it were introduced, influenced by ancient civilizations. The phenomenon of the spread of amulets was considered a way of life that arose out of necessity, as humans believed that they possessed supernatural powers that could protect them from diseases, crises, and sudden problems. This phenomenon spread among different segments of society and was not limited to a specific group. Kings and their followers believed in it, as did individuals from other social classes, both women and men. This study shed light on the types of amulets, their forms, the purpose of their use, as well as the materials from which they were made.